Energetics of underwater swimming in apnea - Vinetti, G.; Taboni, A.; Fagoni, N.; Tam, E.; Lundby, C.; Ferretti, G. (Medicine & Science in Sports & Exercise, 2025)
Purpose Dynamic apnea with fins (DYN) involves swimming the longest distance relying solely on the body`s oxygen and anaerobic energy stores. The energy cost per unit distance (C) is therefore an important determinant of DYN performance, yet it has never been measured. This study aimed to assess the C of DYN and its aerobic (EO2), anaerobic lactic (ELa), and alactic (EPCr) energy contributions.